Living through unsuccessful conception attempts: a grounded theory of resilience among women undergoing fertility treatment. (8th August 2017) - Bailey, Anna; Ellis-Caird, Helen; Croft, Carla
Abstract: Objective: To provide a model of resilience among women undergoing fertility treatments, who experience repeated unsuccessful conception attempts. Background: Assisted reproductive treatment is emotionally and physically challenging. Women undergoing such treatments report experiencing high levels of anxiety and depression. There continues to be a lack of understanding of the process women go through to adapt to the challenges associated with fertility treatment, in order to continue to pursue their goal of pregnancy. Method: The study employed a qualitative Grounded Theory design. Eleven women aged between 24 and 42 years took part in individual semi-structured interviews around their experiences of living through unsuccessful fertility treatment attempts. Results: Three core categories were identified: 'Appraisal'; 'Stepping away from treatment'; and 'Building self up for the next attempt'. Following the failure of treatment, participants appraised their ability to carry on with further treatment attempts. Those who felt they had depleted their resources through the cycle of attempting pregnancy had taken a step back from the treatment cycle to reconnect with themselves and gather sufficient resources to attempt treatment again. During preparation for the next treatment, participants demonstrated their resilience by taking steps to build up their resources, such as nurturing their strength and taking control of their fertility experience. Conclusions: Women undergoing fertility treatment demonstrate their resilience through a variety of actions that enable them to continue to pursue their pregnancy goal. Clinical staff should be mindful of their clients' need to withdraw from the treatment cycle and offer support to enable them to do this.